Pengaruh Kualitas Produk dan Strategi Promosi Online terhadap Minat Beli Konsumen pada UMKM Kue Bawang Buk Masnah di Desa Pekan Tolan - Muhammad Hasbi Sir; Basyarul Ulya; Jeni Sukmal (MANABIS: Jurnal Manajemen dan Bisnis, 2025)
The purpose of this study is to analyze the influence of product quality and online promotion strategies on consumer buying interest in Kue Bawang Buk Masnah MSMEs in Pekan Tolan Village. In the increasingly growing digital era, MSMEs face great challenges in maintaining competitiveness. Therefore, understanding the factors that influence consumer buying interest is very important. The research method used is quantitative and the approach is the associative approach. The data collection process was carried out by distributing questionnaires for 30 consumers of Buk Masnah Onion Cake. Meanwhile, the data analysis technique used is multiple linear regression to measure the extent to which product quality and online promotion strategies affect consumer buying interest. The results of the study show that product quality has a positive and significant effect on consumer buying interest. Factors such as taste, texture, durability, and product packaging prove to play an important role in purchasing decisions. In addition, effective online promotion strategies through social media, marketplaces, and digital advertising have been proven to increase product exposure and strengthen consumer engagement. Therefore, it is important to consistently improve product quality and optimize digital promotion strategies in order to achieve a wider market coverage while strengthening customer loyalty